Pengaruh Harga, Kualitas Produk, Dan Promosi Terhadap Keputusan Pembelian Marketplace Shopee (Pada Pengguna Kota Jogja) - Elvan Septa Indrianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
E-commerce is growing rapidly, including Shopee. Many consumers flock to shop online through Shopee. Because besides being practical it also saves time and energy. This study aims to examine the effect of price, product quality, and promotion on purchasing decisions for the Shopee Marketplace for users in the city of Jogja Primary data was collected through distributing questionnaires to 100 respondents. The sampling technique used was purposive sampling. The data collection technique used a questionnaire, the data analysis technique used was validity and reliability. The data was analyzed using the classical assumption test technique, multiple linear regression analysis, F test, t test, and the coefficient of determination Based on the test results obtained the results of a significant influence with a positive direction from the product quality price variable, and promotion on the purchasing decision variable. Keywords: Price, Product Quality, Promotion, Jogja City Users